Method for sintering porous microcrystalline glass with open pore structure by using granite sludge loose powder

By mixing granite mud and green silicon carbide, using high-temperature instantaneous sintering and low-temperature diffusion sintering processes, porous crystallized glass with an open pore structure is formed, which solves the problem of closing the pore structure of existing porous crystallized glass and achieves high performance The application of building materials and sewage purification treatment has improved the utilization rate and added value of granite mud.

CN119320238APending Publication Date: 2025-01-17NANCHANG HANGKONG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411510098.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The porous structure of existing porous microcrystalline glass is mainly closed pores, which limits its application field and cannot fully utilize the resource value of granite sludge.

Method used

Using a mixture of granite sludge and green silicon carbide as a foaming agent, porous crystallized glass with an open pore structure is formed through high-temperature instant sintering and low-temperature diffusion sintering processes.

Benefits of technology

The open-pore structure of porous crystallized glass is realized, which has the characteristics of high porosity, heat insulation, sound insulation and humidity adjustment. It is suitable for high-performance building energy-saving materials and sewage purification treatment, and improves the utilization rate and added value of granite mud.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320238A_ABST
    Figure CN119320238A_ABST
Patent Text Reader

Abstract

The invention discloses a method for sintering open-pore structure glass ceramics from granite sludge loose powder, which belongs to the field of energy-saving building materials and comprises the following process steps: (1) mixing green silicon carbide serving as a foaming agent with granite sludge powder to obtain uniform mixed powder; (2) granulating the mixed powder, and uniformly spreading the granulated mixed powder in a refractory mold; (3) putting the refractory mold into a muffle furnace, and carrying out instantaneous sintering at high temperature, so that contact points of adjacent particles form welding points; and performing diffusion sintering at a low temperature, and forming rigid connection pore channels among particles through mass transfer diffusion of fusion points to prepare the porous microcrystalline glass with an open pore structure. The granite sludge powder has the characteristics of high utilization rate, simple and convenient production process, low production cost, adjustable porosity and the like, is suitable for producing large-size and complex-shape porous microcrystalline glass, has the characteristics of heat insulation, sound insulation, humidity adjustment and the like, is expected to be applied to high-performance lightweight wall materials and sewage purification treatment, and has wide application prospects. The high-value utilization of the granite sludge is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy-saving building materials, and in particular relates to a method for sintering open-pore porous microcrystalline glass with loose powder of granite mud residue. Background Art

[0002] Granite is widely used in the field of building decoration materials. A large amount of mud is produced during the mining and processing of granite. Simple accumulation or landfill not only occupies precious land resources, but also causes potential harm to soil, air and water resources. The resource utilization of granite mud has important economic and ecological benefits.

[0003] Granite waste is currently mainly used in green building materials (concrete, geopolymers and environmentally friendly bricks, etc.), fine ceramics, composite materials and microcrystalline glass (Research Progress on Resource Utilization of Granite Waste [J]. Chemical Minerals and Processing 2023; 52(3): 45-52+59). Although there are many studies on the resource utilization of granite waste at home and abroad, the added value is low and the economic benefits are limited, and the enthusiasm of related industries is not high. In recent years, foam ceramics made from solid waste have become an increasingly popular environmentally friendly material due to their excellent properties such as porosity, light weight, thermal insulation and sound insulation. At present, they are widely used in building cladding, noise reduction, filtration, separation and other fields (Effect of process parameters on characteristics and pore structure of foam ceramics prepared from granitesawing dust [J]. Ceramics International, 2024; 50(5): 8378-8389). Granite waste has similar physical and mineralogical characteristics to foam ceramic raw materials.

[0004] For preparing porous microcrystalline glass from granite waste residue, the waste residue is evenly mixed with a foaming agent, pressure-formed into a blank, and after sintering and foaming, porous microcrystalline glass is formed. Patent CN118373665A discloses a full-solid waste foam ceramic insulation material and a preparation method thereof, wherein granite waste stone powder, fly ash, carbide slag, marble waste stone powder, glass waste residue, etc. are mixed with water to obtain a mixture, which is pressure-formed in a mold to obtain a blank, and the blank is dried and sintered to obtain a full-solid waste foam ceramic insulation material. Patent CN109553304A discloses a slag porous microcrystalline glass and a preparation method thereof, wherein the slag porous microcrystalline glass raw materials include basic glass powder, a binder and a pore-forming agent, the raw materials are mixed according to a suitable mass ratio, pressure-formed after drying, sintered and impregnated at low temperature for a long time to form primary pores, and then heated and insulated for a second time to complete the nucleation, crystallization and foaming processes to form uniform secondary pores, and obtain graded porous microcrystalline glass.

[0005] At present, the porous glass-ceramics sintered from silicate solid waste basically have closed pores, that is, the pores are surrounded by a dense matrix and the pores are not connected. The application field of this porous glass-ceramics with closed pore structure is very limited and is only suitable for thermal insulation materials. In contrast, porous glass-ceramics with open pore structure have the characteristics of heat insulation, sound insulation and humidity regulation. They have a wide range of applications in high-performance building energy-saving materials and sewage purification, and help to achieve high added value utilization of granite mud. Summary of the invention

[0006] The object of the present invention is to provide a method for sintering open-pore porous glass-ceramics with loose powder of granite mud, which is different from the closed-pore porous glass-ceramics formed by traditional pressure molding and sintering. The present invention uses granite mud as the main raw material and green silicon carbide as the foaming agent. After the foaming agent is mixed with the granite mud and granulated, it is evenly spread in a refractory mold, and then instantaneously sintered at high temperature and diffused sintered at low temperature to prepare a porous glass-ceramics with an open-pore structure. The present invention has the characteristics of abundant raw material sources, high utilization rate of granite mud, simple production process, low production cost, adjustable porosity, etc. It is suitable for the production of porous glass-ceramics of large size and complex shape, and has the characteristics of heat insulation, sound insulation and humidity regulation. It is expected to be applied to high-performance lightweight wall materials and sewage purification, and realize the high-value utilization of granite mud.

[0007] The present invention firstly melts part of the feldspar mineral in the granite during instantaneous sintering at high temperature to form a small amount of liquid glass phase, forming a fusion point between adjacent particles as the skeleton base point of the open-porous structure; then, the feldspar in the granite continues to melt during diffusion sintering at low temperature to form more glass phase, and the skeleton base point grows through mass transfer and diffusion of the fusion point, strengthening the skeleton structure and forming a rigid connection channel of the open-porous structure. During the sintering process, the green silicon carbide is oxidized, and most of the generated carbon dioxide and carbon monoxide gas will be discharged from the matrix through the formed open-porous channels. During the gas discharge process, the skeleton is densified, which plays a role in strengthening the skeleton.

[0008] A method for sintering open-pore porous glass-ceramics from loose powder of granite mud residue, the process steps of which are as follows: Mix the foaming agent and granite mud evenly, and sieve through an 80-mesh sieve to obtain a uniform mixed powder; After the mixed powder is granulated, it is evenly spread in a refractory mold coated with alumina; The refractory mold is placed in a muffle furnace for high-temperature instantaneous sintering, and then low-temperature diffusion sintering to prepare a porous micro-ceramic glass with an open-pore structure; The foaming agent is green silicon carbide, and its usage amount is 1% to 3% of the mass of granite mud.

[0009] The particle size of the mixed powder granulation is 40 to 120 meshes.

[0010] The sintering temperature of the high-temperature instantaneous sintering is 1120-1180°C, and no insulation is required; the sintering temperature of the low-temperature diffusion sintering is 1050-1100°C, and the sintering time is 10-30 minutes.

[0011] Compared with porous ceramics with closed pore structures, the present invention utilizes loose powder to sinter porous microcrystalline glass with open pore structures, which has substantial progress and innovation in preparation method and pore structure: (1) Granite slag powder is used as the main raw material, and the loose powder sintering method is adopted. There is no need for pressure molding and it is not limited by the mold size. It is suitable for the production of large-sized and complex-shaped porous micro-ceramics. (2) The present invention adopts a loose powder sintering method, through high-temperature instantaneous sintering, to form a fusion point at the contact point of adjacent particles, combined with low-temperature diffusion sintering, through mass transfer and diffusion at the fusion point, to form a rigid channel, thereby obtaining a porous microcrystalline glass with high porosity and an open-pore structure; (3) The role of the foaming agent in the present invention is that the green silicon carbide is oxidized to generate gas during the sintering process, which inhibits particle sliding and filling and prevents pore collapse; at the same time, when the gas is discharged through the pores, the pores are densified under the action of gas pressure, thereby obtaining a porous microcrystalline glass with a higher specific compressive strength.

[0012] In summary, the present invention has high granite mud utilization rate, simple production process, and low production cost. It is suitable for producing porous microcrystalline glass with large size and complex shape, and is expected to be applied to high-performance lightweight wall materials and sewage purification, so as to realize high value-added resource utilization of granite mud. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is the preparation process of porous microcrystalline glass with open pore structure.

[0014] Figure 2 This is a real photo of the porous microcrystalline glass in Example 1.

[0015] Figure 3 This is the XRD spectrum of the porous glass-ceramics in Example 1.

[0016] Figure 4 This is the SEM photo of the porous glass-ceramics in Example 1.

[0017] Figure 5 This is an X-CT photograph of the porous microcrystalline glass in Example 1. DETAILED DESCRIPTION

[0018] The present invention is further described by the following specific implementation examples, but the content of the present invention is not limited to the content involved in the examples.

[0019] The process flow of preparing the porous glass-ceramics with open-pore structure by sintering the loose powder of granite mud residue of the present invention is as follows: Figure 1 As shown, green silicon carbide is used as a foaming agent and mixed with granite mud to obtain a uniform mixed powder. After the mixed powder is granulated, it is evenly spread in a refractory mold coated with an alumina coating. The refractory mold is placed in a muffle furnace for high-temperature instantaneous sintering, so that the contact points of adjacent particles form welding points; then, low-temperature diffusion sintering is performed, and the welding points grow through mass transfer diffusion, forming rigid connection channels between particles, and preparing porous microcrystalline glass with an open-pore structure.

[0020] Example 1 0.6 g of green silicon carbide and 30 g of granite slag powder were weighed and mixed in an agate mortar. The mixed powder was passed through an 80-mesh sieve and evenly spread in a refractory mold coated with an alumina coating. The refractory mold was placed in a muffle furnace and sintered at 1150°C for an instantaneous high temperature (without heat preservation). Then, it was diffusely sintered at 1080°C for 30 min to obtain an open-pore porous glass-ceramic. The compressive strength of the sintered sample was tested on a ceramic bending tester and was 23.5 MPa. The water absorption rate was 21.6% and the volume density was 1.66 g / cm by the Archimedes drainage method. 3 The true density of the porous glass-ceramics was tested by the pycnometer method, and the apparent density of the porous glass-ceramics was calculated based on the mass and volume. The porosity calculated from the true density and the apparent density was 32.4%.

[0021] Figure 2 This is a photo of a porous glass-ceramic with an open-pore structure. It can be seen that the micropores are evenly distributed on the surface. The crystal structure of the porous glass-ceramic is analyzed by powder X-ray diffraction (XRD). Figure 3 The main crystal phases of glass-ceramics are quartz, calcium feldspar and albite. The microstructure is observed by scanning electron microscopy (SEM). Figure 4 As shown in Figure 1, the pore structure is an open pore structure, the pore walls between particles are dense and coarse, and the pore size is mainly between 10 and 100 mm. The overall morphology was observed using an X-ray computed tomography system (X-CT). Figure 5 As shown, the pore size of the open-pore structure is uniform, forming a network of pore channels.

[0022] Example 2 Weigh 0.6 g of green silicon carbide and 30 g of granite slag powder in an agate mortar, and mix the mixed powder through an 80-mesh screen; the mixed powder is granulated with a polyvinyl alcohol aqueous solution and then sieved through an 80-mesh screen; after drying, the granulated powder is evenly spread in a refractory mold coated with an alumina coating; the refractory mold is placed in a muffle furnace and sintered at 1150 °C for an instantaneous high temperature (without heat preservation); then diffusely sintered at 1100 °C for 20 min to obtain an open-pore porous microcrystalline glass. The compressive strength of the microcrystalline glass was tested on a ceramic bending tester, which was 20.6 MPa; the water absorption rate was 30.8% and the volume density was 1.62 g / cm by the Archimedes drainage method. 3 The true density of the porous glass-ceramics was tested by the pycnometer method, and the apparent density of the porous glass-ceramics was calculated based on the mass and volume. The porosity calculated from the true density and the apparent density was 43.2%.

[0023] Example 3 Weigh 0.9 g of green silicon carbide and 30 g of granite slag powder in an agate mortar, and mix the mixed powder through an 80-mesh screen; the mixed powder is granulated with a polyvinyl alcohol aqueous solution and passed through a 120-mesh screen; after drying, the granulated powder is evenly spread in a refractory mold coated with an alumina coating; the refractory mold is placed in a muffle furnace and sintered at 1140 °C for an instantaneous high temperature (without heat preservation); then diffusely sintered at 1060 °C for 30 min to obtain an open-pore porous microcrystalline glass. The compressive strength of the microcrystalline glass was tested on a ceramic bending tester, which was 16.3 MPa; the water absorption rate was 35.8% and the volume density was 1.60 g / cm by the Archimedes drainage method. 3 The true density of the porous glass-ceramics was tested by the pycnometer method, and the apparent density of the porous glass-ceramics was calculated based on the mass and volume. The porosity calculated from the true density and the apparent density was 50.7%.

[0024] Example 4 Weigh 0.9 g of green silicon carbide and 30 g of granite slag powder in an agate mortar, and pass the mixed powder through an 80-mesh screen; the mixed powder is granulated with a polyvinyl alcohol aqueous solution and passed through a 120-mesh screen; after drying, the granulated powder is evenly spread in a refractory mold coated with an alumina coating; the refractory mold is placed in a muffle furnace and sintered at 1180 °C for an instantaneous high temperature (without heat preservation); then diffusely sintered at 1100 °C for 30 min to obtain an open-pore porous microcrystalline glass. The compressive strength of the microcrystalline glass was tested on a ceramic bending tester, which was 25.6 MPa; the water absorption rate was 39.6% and the volume density was 1.64 g / cm by the Archimedes drainage method. 3 The true density of the porous glass-ceramics was tested by the pycnometer method, and the apparent density of the porous glass-ceramics was calculated based on the mass and volume. The porosity calculated from the true density and the apparent density was 45.4%.

[0025] It should be pointed out that various improvements and modifications made by technicians in the technical field to the described specific embodiments or replacements with similar methods shall fall within the protection scope of the present invention as long as they do not deviate from the concept of the invention or exceed the scope defined by the claims.

Claims

1. A method for sintering open-pore porous glass-ceramics from loose powder of granite mud, the process steps of which are as follows: S1. The foaming agent and the granite mud are mixed evenly, and sieved through an 80-mesh sieve to obtain a uniform mixed powder; S2. The mixed powder obtained in step 1 is granulated and evenly spread in a refractory mold coated with an alumina coating; S3. Place the refractory mold in a muffle furnace for high-temperature instantaneous sintering, and then perform low-temperature diffusion sintering to prepare a porous microcrystalline glass with an open-pore structure.

2. The method according to claim 1, characterized in that: In step S1, the foaming agent is green silicon carbide, and the usage amount thereof is 1% to 3% of the mass of the granite mud.

3. The method according to claim 1, characterized in that: In step S2, the particle size of the mixed powder granulation is 40-120 meshes.

4. The method according to claim 1, characterized in that: In step S3, the sintering temperature of high-temperature instantaneous sintering is 1120-1180°C, and no insulation is required; the sintering temperature of low-temperature diffusion sintering is 1050-1100°C, and the sintering time is 10-30 minutes.

Citation Information

Patent Citations

  • Slag porous glass-ceramic and preparation method thereof

    CN109553304A

  • All-solid waste foamed ceramic thermal insulation material and preparation method thereof

    CN118373665A